Recent advances in crosstalk between N6-methyladenosine (m6A) modification and circular RNAs in cancer - Xin Huang; Haoyu Guo; Lutong Wang; Lingkai Yang; Zengwu Shao; Weiyue Zhang (Elsevier, 2022)
N6-methyladenosine (m6A), as the most common RNA modification, plays a vital role in the development of cancers. Circular RNAs (circRNAs) are a class of single-stranded covalently closed RNA molecules. Recently, m6A modification has been identified as performing biological functions for regulating circRNAs. Increasing evidence also shows that circRNAs are involved in cancer progression by targeting m6A regulators. In this review, we describe the functional crosstalk between m6A and circRNAs, and illustrate their roles in cancer development. m6A methylation mediates the biogenesis, stability, and cytoplasmic export of circRNAs in different cancer types. Moreover, circRNAs regulate the expression of m6A regulators, participate in the degradation of m6A regulators, and regulate the m6A modification of target mRNAs. Finally, we discuss the potential applications and future research directions of m6A modification and circRNAs in cancer. Further understanding of the biological roles of m6A and circRNAs will provide new insight into the diagnosis and treatment of cancer patients.